Application of person-organization fit in nursing management (个人与组织契合度在护理管理中的应用) - HU Xin (胡馨); GUO Guiying (郭桂英); DUAN Shengbin (段胜斌); YANG Jingyi (杨静怡); HUANG Shiyu (黄始玉) (中西医结合护理)
The person-organization fit reflects the degree of consistency between individuals and organizations at different levels. This paper reviews the concepts and measurement tools of person-organization fit, discusses its current situation in the field of nursing management, and analyzes the influencing factors and enlightenment of person-organization fit, so as to provide reference for nursing management. (个人组织契合度反映了个人与组织在不同层面上的一致程度。本研究对其概念、测量工具以及其在护理管理领域的应用现状进行总结, 并分析个人与组织契合度的影响因素, 以期为进一步改善护理工作环境、护理人员职业认同感等提供参考。)